ÙƒØªØ¨ Ø§Ù„ØªØ±Ø§Ø« ÙˆØ·Ø±Ù‚ ØªØ¯Ø±ÙŠØ³Ù‡Ø§ ÙÙŠ Ø§Ù„Ù…Ø¹Ø§Ù‡Ø¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¨Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ - Iwan Hadi Saputra; Salimul Jihad; Suparmanto Suparmanto; Musthafa Bin Che Omar (Lughatu Ad-Dhat, 2022)
Learning the yellow book or the book of turats in Indonesian Islamic boarding schools is an inseparable element in an Islamic boarding school. Therefore, the right and appropriate learning methodology is very supportive of the succes sof a learning process, especially in learning the turats book. This study aimsto describe the yellow book learning method scommonly used in Islamic boarding schools in Indonesia. The research methodology used in this study is a literature review, where research erscollect data sources from previous studies and collect one by one all methodologi escommonly used in Islamic boarding schools in Indonesia. The result soft his literature review study indicate that the application of the yellow book learning method in Islamic boarding schoolsis in accordance with the methods in herited from generation to generation from the Salaf scholars and academic experts, including: 1) the classical method (a combination of conventional methods) whose learning is tiered and graded, 2) the bandongan method, namely the students listen or follow what is conveyed by the teacher, 3) the sorogan method, namely the teacher listens or follows what is conveyed by the students, but this method is usually for students who are considered sufficient in their knowledge, especially for students who aspireto become a kyaiorustadz 4) the discussion method as a method for problem solving, 5) the memorization method as a method for remembering the material that has beentaught, 6) the question and answer method is a method in education where the teacher asks and students answer about the material they want tolearn. obtained, 7) The lecture method is anexplanation or explanation verbally by the teacher to the students in theclass, 8) the demonstration method is a teaching method in which the teacher or other people who are intentionally asked or the students them selves show the whole class about a learning process that has been carried out, and 9) the Amtsilati method, which his a combined method of memorization methods, fast formulas, and use slot so fex amples from the verses of the Qur'an.